Penyelesaian Hukum Adat Terhadap Tindak Pidana Perzinaan Dalam Keluarga Di Kota Jambi - Hidayat, Iman; Idrah, Chairul; Ambarini, Siti Nur (Wajah Hukum, 2023)
This article discusses the customary law resolution of the crime of adultery within the family in Jambi City, so that the aim is to analyze the problems encountered and efforts to overcome them. The approach used refers to the Socio Legal Research approach. The results of this research show that the resolution of cases of adultery in the family in Jambi City is carried out using customary criminal law which originates from the basis of Jambi customary law, namely by expulsion from the village. fruit and bushes are as sweet as can be. Then the perpetrator apologized for his actions and signed a peace agreement (Surat setih). The problems encountered were differences of opinion between the young people and the elders of Tengganai in traditional meetings in deciding sanctions for this case, adultery cases which were resolved by criminal law. Nationally, the legal process takes a long time and is expensive, causing a lot of suffering to the perpetrators, the community does not know much about the basics of Jambi Customary Law. Efforts to overcome the problems that occur include holding a personal approach from the young people with the elders of Tengganai to continue to enforce the existing criminal law, all parties discussing that customary criminal law is more appropriate than the national criminal law, providing outreach to the community so that they know the basis of Jambi customary law. The suggestion is to ensure that adultery does not occur in the family, namely providing religious counseling so that faith is strengthened rather than lust and basic counseling on Jambi customary law so that the public knows that customary criminal law can resolve cases of family adultery quickly, at an affordable cost, thus the existence of criminal law. Customs are valid and have permanent legal force.